Aplikasi Agensia Hayati Metarhizium anisopliae Terhadap Spodoptera frugiperda J. E. Smith - Ramadhani, Roni; Soedijo, Samharinto; Rosa, Helda Orbani (JURNAL PROTEKSI TANAMAN TROPIKA, 2024)
Fall Armyworm (Spodoptera frugiperda) is an invasive insect pest that has a high appetite, causing damage and reduced yields in corn plants. One way to control these larvae is to use the biological agent Metarhizium anisopliae. The aim of this research was to determine the influence of several spore densities of the entomopathogenic fungus M. anisopliae on S. frugiperda. The design used in this research was a Completely Randomized Design (CRD) which consisted of 4 treatment levels of spore suspension density 107,108, 109 and a water control treatment as a comparison with 6 replications. Application was carried out on 3-4 instar larvae with an observation period of 12 hours for 4 days. The results of this study showed that the application of the biological agent M. anisopliae with a spore density treatment of 109caused the highest larval mortality of 76.7%. Lethal time (LT_50) for larval mortality caused by M. anisopliae is 2.80 days. From probit analysis, the Lethal Concentration (LC_50) value was 2.44 x 109 spores/ml.